Interface characterisation of diffusion bonded Ti-6Al-4V alloy and austenitic stainless steel couple - Kurt, B.; Orhan, N.; Kaya, M. (Maney Publishing, 2009)
In this study, the Ti-6Al-4V alloy was diffusion bonded to austenitic stainless steel at temperatures of 820, 885, 930 and 980 degrees C, under a pressure of 5 MPa for 30 min. The effect of temperature on interface formations and microstructure was investigated using a scanning electron microscope (SEM), energy dispersive spectrograph (EDS) microanalyses, X-ray diffraction and shear strength of bonded specimens. The results showed that intermetallic phases and sigma-phase formed in the interface region.
Keywords: Interface characterisation; Diffusion bonding; Ti-6Al-4V; Austenitic stainless steel